Investigation of granulometric parameters in wind erosion studies (Case study:Gonabad) - Malihe Mohamadnia; Abolghasem Amirahmadi; MohamadAli ZanganeAsadi (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this research is to use granulometric analyzes in desertification studies in Gonabad city,  To achieve this goal, after the preparation of geomorphological maps of the region, 14 sediment samples were taken from the erosion-sensitive facies of the region. In the laboratory, a series of sieve with a diameter of 2000, 1000, 500, 250, and 64 micrometers, and a container Gatherings of sediment smaller than 64 μm were screened. The results showed that the highest frequency of particle diameter in sand samples was in the 250-225 micron class. And, given the average particle relationship with their transport intervals, it can be concluded that the distance between the particles was close to a point. Variants of different samples varied from 1.502 to 1.319. The most prevalent plots of ridge and the smallest slopes with low slope were the highest. In surveys in the skidding section, precipitates were mostly positive tilted, indicating the prevalence of fine particles in the region.